2004
DOI: 10.1023/b:phar.0000013464.09197.41
|View full text |Cite
|
Sign up to set email alerts
|

Unclaimed prescriptions after automated prescription transmittals to pharmacies

Abstract: Primary non-compliance was generally low, but there were differences related to age, gender and type of drugs. The most common reason reported for non-redemption was that the prescription was not needed, but some patients were unaware that prescriptions were issued and transmitted to the pharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 13 publications
5
81
1
2
Order By: Relevance
“…Det datoriserade receptet, som på elektronisk väg förs från läkarens dator direkt till apotekets skrivare, förenklar recepthanteringen och besparar läkaren tid. Det finns enstaka studier som visar att den primära följsamheten inte försämras av elektroniska recept (140). Men det personliga överlämnandet av receptet, som står för ett omhändertagande -en "ritual", försvinner med elektroniska recept och möjligheterna till personlig dialog med farmaceuten begränsas om medicinerna sänds per post till patienten.…”
Section: Den Personlige Läkarenunclassified
“…Det datoriserade receptet, som på elektronisk väg förs från läkarens dator direkt till apotekets skrivare, förenklar recepthanteringen och besparar läkaren tid. Det finns enstaka studier som visar att den primära följsamheten inte försämras av elektroniska recept (140). Men det personliga överlämnandet av receptet, som står för ett omhändertagande -en "ritual", försvinner med elektroniska recept och möjligheterna till personlig dialog med farmaceuten begränsas om medicinerna sänds per post till patienten.…”
Section: Den Personlige Läkarenunclassified
“…This is similar to previous research on unclaimed prescriptions in which the classes most frequently reported as having the highest percentage of unclaimed scripts included psychiatric medications (sometimes called central nervous system [CNS] drugs), analgesics, contraceptives, and antibiotics. 1,[3][4][5]7,8,[10][11][12][13][14][15]20,26,27,41,[47][48][49] Differences in research methods between the present study and previous research may explain why antibiotics, which comprised 1.6% of unclaimed fills, were not among the top 3 unclaimed prescription classes reported for this research population. By using 12 months of data on prescription drug orders and dispensings, the present study was not affected by seasonal drug utilization that is likely more common for antibiotics than other drug classes, while other studies that use fewer than 12 months of data (in some cases, 1 or 2 months) are potentially more affected by seasonal patterns of drug use.…”
Section: ■■ Discussionmentioning
confidence: 82%
“…The levels of unclaimed prescriptions across drug classes primarily associated with chronic and acute medical conditions were examined because unclaimed prescriptions most often are associated with use of medications for acute conditions. 1,[3][4][5]7,8,[10][11][12][13][14][15]20,26,27,41 ■■ Results Between May and July 2004, telephone interviews with 1,214 TRICARE beneficiaries were completed, with a response rate of 60.6% (attempts were made to contact 2,004 patients in total to reach a target of 200 completed interviews per study pharmacy). From March to July 2004, respondents filled nearly 7 prescriptions, on average.…”
Section: Analysis Of Survey Datamentioning
confidence: 99%
See 1 more Smart Citation
“…those that network prescribing and dispensing computer systems [24]. Even fewer studies address the computerisation of transmission as their primary objective, and these are mainly focused on the receiving end of the transmission process, in pharmacies, and not specifically on its effects on workload or efficiency of clinical practice [25][26][27]. Thus the evidence on time-savings and efficiency gains achieved by making the transmission of prescriptions electronic is ambiguous and often incidental, emerging out of studies of computerisation of prescribing in general, rather than specifically of transmission of prescriptions.…”
Section: Box 2 -Electronic Prescriptionmentioning
confidence: 99%